2022
DOI: 10.1038/s41598-022-15279-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ultra-rare genetic variants in pediatric acute onset neuropsychiatric syndrome (PANS) by exome and whole genome sequencing

Abstract: Abrupt onset of severe neuropsychiatric symptoms including obsessive–compulsive disorder, tics, anxiety, mood swings, irritability, and restricted eating is described in children with Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS). Symptom onset is often temporally associated with infections, suggesting an underlying autoimmune/autoinflammatory etiology, although direct evidence is often lacking. The pathological mechanisms are likely heterogeneous, but we hypothesize convergence on one or more biologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 121 publications
0
12
0
Order By: Relevance
“…It can represent a trigger for developing PANS symptoms, as already suggested by other research groups ( 15 , 16 ). Regarding etiopathogenesis, a recent study ( 17 ) suggests a possible genetic role of some “PANS gene” as PPM1D, CHK2, RAG1 , and PLCG2 , highly expressed in peripheral immune responses and microglia and the enteric nervous system and the choroid plexus. Genetic variation in PANS candidate genes may function by disrupting peripheral and central immune functions, neurotransmission, and/or the blood-CSF/brain barriers following stressors such as infection.…”
Section: Discussionmentioning
confidence: 99%
“…It can represent a trigger for developing PANS symptoms, as already suggested by other research groups ( 15 , 16 ). Regarding etiopathogenesis, a recent study ( 17 ) suggests a possible genetic role of some “PANS gene” as PPM1D, CHK2, RAG1 , and PLCG2 , highly expressed in peripheral immune responses and microglia and the enteric nervous system and the choroid plexus. Genetic variation in PANS candidate genes may function by disrupting peripheral and central immune functions, neurotransmission, and/or the blood-CSF/brain barriers following stressors such as infection.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, concerns for a possible neuroinflammatory complication of this condition have emerged, with three people having unexplained developmental regression. One individual was diagnosed with Pediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcal infections (PANDAS) at age 6 (Trifiletti et al, 2022), one experienced loss of language at age 16, and one had recurrent episodes of inability to walk and regression of other skills at age 6–7. A unifying etiology for these abnormalities has not been uncovered.…”
Section: Resultsmentioning
confidence: 99%
“…As ES is now recommended as a first‐line test for those with intellectual disability (Manickam et al, 2021), it is likely that additional novel variants in other exons of this gene will be identified, and the clinical features seen in our cohort differentiated from the features seen with variants in other exons. To date, the features seen in those with pathogenic variants in other exons seem generally dissimilar to those seen with variants in exons 5 and 6 and should not be confused with JdVS (Trifiletti et al, 2022). Further research into the manifestations of damaging germline variants in exons 1–4 of PPM1D is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying genes that underlie PANDAS/PANS and studying their effect on the immune system and neuronal function in cell lines, animal models, and peripheral blood mononuclear cells could potentially identify novel genetic and molecular biomarkers. While the field is still in its infancy, there is one published genetic analysis that used whole genome and whole exome sequencing to identify ultra-rare genetic variants in PANS [75]. This study identified a heterogeneous mix of genetic variants affecting immune and glutamatergic neuronal function.…”
Section: Autoantibodies and Proinflammatory Monocytesmentioning
confidence: 99%